2021
DOI: 10.3389/fimmu.2021.705543
|View full text |Cite
|
Sign up to set email alerts
|

Partially Hydrolysed Whey Has Superior Allergy Preventive Capacity Compared to Intact Whey Regardless of Amoxicillin Administration in Brown Norway Rats

Abstract: BackgroundIt remains largely unknown how physicochemical properties of hydrolysed infant formulas influence their allergy preventive capacity, and results from clinical and animal studies comparing the preventive capacity of hydrolysed infant formula with conventional infant formula are inconclusive. Thus, the use of hydrolysed infant formula for allergy prevention in atopy-prone infants is highly debated. Furthermore, knowledge on how gut microbiota influences allergy prevention remains scarce.ObjectiveTo gai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 67 publications
1
20
0
Order By: Relevance
“…We previously reported that amoxicillin promotes classical FoxP3 + CD25 + Treg cells in the SI, but not in the blood, mLN or PP after a short 1‐week regimen of daily administrations in BN rats 28 . However, this effect seems only to be transient, as amoxicillin did not affect the overall frequency of classical FoxP3 + CD25 + Tregs in the intestine five weeks after a 4‐week regimen of daily administrations in BN rats 25 . Combined, the findings indicate that amoxicillin has limited long‐term effects on homeostatic immune regulation and risk for food allergy development in the gut.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…We previously reported that amoxicillin promotes classical FoxP3 + CD25 + Treg cells in the SI, but not in the blood, mLN or PP after a short 1‐week regimen of daily administrations in BN rats 28 . However, this effect seems only to be transient, as amoxicillin did not affect the overall frequency of classical FoxP3 + CD25 + Tregs in the intestine five weeks after a 4‐week regimen of daily administrations in BN rats 25 . Combined, the findings indicate that amoxicillin has limited long‐term effects on homeostatic immune regulation and risk for food allergy development in the gut.…”
Section: Discussionmentioning
confidence: 91%
“…The main adverse reaction to amoxicillin treatment is diarrhoea, 22 which likely can be attributed to the disturbance of the gut microbiota composition in humans 23,24 . We previously found that amoxicillin did not affect the development of oral tolerance to cow's milk whey protein concentrate (WPC) in a Brown Norway (BN) rat model of CMA 25 . This finding indicates that this particular antibiotic does not promote food allergy by inhibiting homeostatic tolerance induction in the gut.…”
Section: Introductionmentioning
confidence: 99%
“…Results from animal studies are in line with the results from human studies, with some studies showing a preventive effect of pHFs on CMA development, while other studies did not show such effect. For example, studies by Graversen et al, Jensen et al, and Fritsche et al showed that partially hydrolysed whey had a capacity to induce oral tolerance to intact whey proteins [ 151 , 162 , 163 ]. Further, Chikhi et al showed that partially hydrolysed whey induced a partial prevention of sensitisation to β-lactoglobulin but no prevention of sensitisation to caseins [ 164 ].…”
Section: Cow’s Milk-based Infant Formulasmentioning
confidence: 99%
“…For example, lack of the preventive effect of partially hydrolysed whey on casein sensitisation development may be explained by the lack of casein derived peptides in this type of product and, as a consequence, lack of the oral tolerance induction towards caseins as explained in the study by Chikhi et al [ 164 ]. In addition, different pHFs characteristics may be explained by the huge variation in DH, as illustrated by Graversen et al [ 162 ].…”
Section: Cow’s Milk-based Infant Formulasmentioning
confidence: 99%
“…A role for glutamine in the preservation of intestinal health and in the promotion of intestinal growth and barrier function is further supported by the findings of studies in young animals. For instance, in piglets, dietary glutamine supplementation protected against E.coli-and endotoxin-induced intestinal damage [114,119,120]. Moreover, dietary Whether dietary glutamine can also prevent bacterial translocation in neonatal animals, however, remains to be examined.…”
Section: Impact Of Glutamine On Intestinal Functionsmentioning
confidence: 99%